Is there Shalom, or not? Jeremiah, a prophet for South Africa - Fischer, Georg (Old Testament essays, 2015)
There is a dispute between prophets about the status of Jerusalem and its society. The Book of Isaiah, on various occasions, sees the city and its people full of shalom "peace, well-being" (Isa 26 : 3; 32 : 18). The Book of Jeremiah, on the other hand, negates such a vision and accuses colleagues announcing such a message of "deceit" (Jer 6 : 13 - 14). The book is outstanding in its focus on the grievances leading to the fall of Jerusalem; its profile is marked by calling things as they are, analyzing the roots of evil, and disclosing the broken relationship with God as one of the causes. Such acritique has consequences : Jeremiah has to suffer, more than any other colleague. Nevertheless he, too, proclaims shalom (e.g. Jer 29 : 11), but it is rooted in a new perception of an inwardly touched God who desires eagerly to bring about a change to those who have gone through hardship. This message of the Book of Jeremiah and the figure of the prophet have a bearing for South Africa : suffering, problems, injustice can all be resolved, if they are addressed in a manner similar to the way in which Jeremiah dared to speak out and to advocate God's view in his own times.,